Genetic analysis of X-linked mutagen-sensitive mutants of Drosophila melanogaster. - Mason, J.M.; Green, M.M.; Shaw, K.E.S.; Boyd, J.B. (Mutation Research, 1981)
Mutants at 2 new loci which control mutagen-sensitivity are described. Mutants of both foci are female-sterile and are hypersensitive to killing by MMS; neither increases the frequency of sex-linked recessive lethals. A screen of previously described female-sterile and meiotic mutants has revealed that a number of these are also sensitive to mutagens. In addition, several new mutants have been identified on the basis of sensitivity to either HN2 or MMS. An analysis of complementation data suggests that all of the X-linked genes controlling sensitivity to MMS may now have been identified. Among the new mei-41 alleles are mutants which show very little meiotic nondisjunction or loss. Cytogenetic mapping of previously known mutants is also described. The mutants mus(1)104D1 and mei-41D5 are located in the region 14B13+/- -14D1,2 on the polytene chromosome map, and they map very close to each other genetically. Cytogenetically mus(1)101D1 is between salivary chromosome bands 12A6,7 and 12D3, mus(1)103D1 is between bands 12A1,2 and 12A6,7 and mus(1)109A1 is in section 8F3--9A2.